Behavioral intention of young consumers towards the acceptance of social media marketing in Emerging Markets - Thao Nguyen Thi Phuong; Anh Nguyen Van (Zielona Góra: Faculty of Economics and Management Press)
The study identifies the factors that influence marketing through social media of users in the Vietnam market, conducted through qualitative and quantitative methods. The research results show that Intention to use social media marketing is directly affected by Attitude towards advertisement and Attitude to electronic words of mouth.
Keywords: social media marketing; EWOM; attitude towards advertisement; intention to use; media społecznościowe; reklama; wykorzystanie reklamy